Tabayyun Resilience: Wikipedia Intervention in Reducing Digital Blind Trust Among Students of SMK UNITOMO Surabaya - Faqih Abdul Aziz; Evi Fatimatur Rusydiyah; Ghazali Mohamed Fadzil (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
The pervasive penetration of digital technology in the digital era has led to digital blind trust among students of Vocational High Schools (Sekolah Menengah Kejuruan/SMK), whereby open encyclopedia platforms are often treated as absolute truth without verification. This quasi-experimental study aims to examine the effectiveness of a forensic investigation intervention targeting Wikipedia's open-editing architecture in reducing digital blind trust and enhancing students' Tabayyun resilience. Employing a nonequivalent control group design, the study involved 44 Grade X students at SMK UNITOMO Surabaya, divided into experimental and control classes. Data were collected through Likert-scale questionnaires administered at the pre-test and post-test phases. Subsequently, they analyzed using N-Gain, Shapiro-Wilk, Levene's Test, Welch's Independent Sample t-test, and Cohen's d. Statistical computations confirmed the statistically significant rejection of the null hypothesis (p < 0.001). The experimental class showed substantial cognitive improvement, with a mean N-Gain of 0.6166, in stark contrast to the control class, which exhibited a regression in competency (N-Gain = âˆ’0.0617). Effect size analysis yielded a Cohen's d value of 4.925, confirming a large intervention effect. In conclusion, direct deconstruction of vulnerabilities in digital information architecture demonstrates strong empirical potential to facilitate the transformation of Tabayyun from a moral recommendation into a measurable self-regulating behavior. These findings underscore the urgency of integrating critical digital literacy into the Islamic Religious Education curriculum as a vocational epistemological safeguard in the twenty-first century.